(untitled) (Comprehensive Journal of Science, 2025)
This study aims to measure the impact of the Libyan Audit Bureau’s commitment to the requirements of the Code of Professional Conduct No. (130) issued by the International Organization of Supreme Audit Institutions (INTOSAI) in reducing financial corruption. To achieve this goal, the descriptive and analytical approach was followed, where the questionnaire was used as a basic means of data collection, which was distributed to the auditors of the State Audit Bureau in the General Administration. After analyzing the data and testing the hypotheses of the study, the conclusion was reached that adherence to the rules of professional conduct has a positive and direct impact on reducing financial corruption through (independence and objectivity, integrity, efficiency, confidentiality and transparency), and accordingly a set of recommendations were made in this regard. Keywords: Code of Conduct, Financial Corruption, Libyan Audit Bureau, International Auditing Standards "INTOSAI."